EFEKTIFITAS TENAGA KERJA PADA PROYEK BANGUNAN - Wijaya, Anton; Arpan, Budiman; Mulyani, Endang (JeLAST : Jurnal PWK, Laut, Sipil, Tambang, 2015)
Labor is an important factor in the implementation of construction projects. Labor used normally not be individuals but in the form of Handyman group consisting of builders and carpenters helper who served in various proportions. One of the factors that need to be considered in assessing the performance of the group was to determine the effectiveness of time handyman work. The study was conducted by comparing the real work time obtained from field measurements with theoretical work time is calculated based on hours of work in general, which is then adjusted existing theories in the literature. Furthermore, the real work time is calculated effectiveness of the theoretical work time, both for the size of each group as well as for overall handyman. Comparisons are also made for the effectiveness with age, experience apes (certain fields and overall). The results obtained show that the effectiveness of the overall working time was 98.24%. Handyman group that has the highest effective working time is Handyman group A with the effectiveness of working time was 98.37%. Keywords: Real Working Time, Work Time Theoretical, Effectiveness, Handyman Group